The Impact of Leadership and Organizational Culture on Health Workers’ Job Satisfaction: An OCB Study at Public Health Centers in Jember - Titis Sulistyowati; Yuly Peristiowati; Ratna Wardani (Ficco Public Health Journal, 2025)
Background: Job satisfaction in the health sector has become an important issue because it is a positive emotional state resulting from a job evaluation. Welfare policies for health professionals in various organizations can play a role, indicating that understanding work policies can affect job satisfaction. This study aims to analyze the influence of leadership and work culture on job satisfaction based on the organizational citizenship behavior (OCB) model on health workers at the Jember Regency Health Center. Methods: This study used a cross-sectional design with the population being health workers at the Jember Regency Health Center. This study involved 128 participants who were determined using simple random sampling techniques. The analysis in this study used logistic regression testing. Results: The results found that health workers reported the most transactional leadership styles (34.4%), clan culture (36.7%), and the level of job satisfaction was mostly low (53.9%). Logistic regression analysis shows that leadership style (OR: 6.155; 95%CI: 2.543-14.89) and work culture (OR: 4.016; 95%CI: 2.393-4.673) have a significant effect on the level of job satisfaction. Conclusions: Building a process of psychosocial change among health workers is necessary for leaders to form and maintain a transformational leadership style and clan culture as an effort to increase job satisfaction.